Radical gastrectomy is safe for treatment of gastric cancer patients on immunosuppressive drugs after organ transplantation - Lee, Jin Ah; Kim, So Jung; Seo, Ho Seok; Lee, Han Hong; Kim, Sung Geun; Jun, Kyong Hwa; Song, Kyo Young; Jung, Yoon Ju (Frontiers in Oncology, 2024)
Background: De novo malignancies are major causes of death after organ transplantation because the recipients subsequently receive immunosuppressant drugs. When gastric cancer develops, the clinical course of the tumor may be particularly aggressive. However, there are few reliable studies of gastric cancer treatment after organ transplantation. This study examined the clinicopathological characteristics of gastric cancer patients after organ transplantation and evaluated treatment outcomes after gastrectomy.Methods: Clinical data were collected from 54 patients who were diagnosed with gastric cancer after organ transplantation. Of these, 30 who underwent surgery for gastric cancer while on immunosuppressant medications were compared with a control group of 625 gastric cancer patients. To compensate for clinical differences between the two groups, 1:1 propensity-score matching was performed.Results: Among the 30 gastric cancer patients on immunosuppressants, kidney transplantation was the most common procedure (19/30, 63.3%) followed by bone marrow (6) and liver transplantation (4); among all 54 patients, 45 were on one or two immunosuppressants. Up-migration to an advanced pathological stage was more frequent in the transplant group. In multivariate analysis, transplantation was a significant risk factor for upmigration from the T, M, and final stages after surgery. When the 30 patients on immunosuppressants who underwent gastric cancer surgery were compared with the matched controls, the total incidence (30.0 vs 40.0%, P = 0.417) and the number of severe postoperative complications (16.7 vs 13.4%, P = 0.417) did not differ significantly between groups after propensity score matching. In terms of overall survival, the transplant group showed significantly worse prognosis in stages I, II, and IV (P < 0.001, P = 0.039 and 0.007, respectively).Radical gastrectomy can be a safe oncological procedure for gastric cancer patients on immunosuppressants after transplantation. Considering their immunosuppressed condition and the possibility of underestimation of the stage of gastric cancer, early detection with endoscopic screening is needed to allow curative treatment.